Peran Pemerintah Provinsi Jawa Tengah Dalam Meresolusi Konflik Proyek Strategis Nasional Di Desa Wadas - Balebat, Rafi; Akbar, Idil (UIR Press, 2024)
The government is an organization that holds authority in compiling and determining it (regeling function), including in agrarian affairs. Apart from having power over regulations related to agrarian matters, the government is also responsible for resolving various disputes or conflicts related to agrarian matters. As happened in Wadas in February 2022. Where there was a demonstration by residents of Wadas Village, Bener District, Purworejo Regency, Central Java. To find out the role of the government in resolving the conflict, the author conducted research using the literature study method by searching, collecting and compiling data from various sources, including journals, books, documentation, the internet and libraries. From the results of this research, it was found that the Central Java Provincial Government resolved the Wadas Village conflict by direct control by opening a discussion forum and a profit compensation clause for Wadas residents who were harmed by the Bener Dam strategic development project (PSN).